Fish Bone Analysis Toward Risk Mitigation of Mushroom Cultivation - I Gusti Ngurah Putu Wahyu Wija Purnama; I Made Budiasa; Ni Gst. Ag. Gde Eka Martiningsih (CV Projurnal Mitra Publikasi, 2025)
Oyster mushroom cultivation has considerable economic potential; however, production activities are inherently exposed to various risks that may disrupt productivity and business sustainability. UD. ARERA Oyster Mushroom in East Denpasar faces recurring production risks, including inconsistent baglog quality, unstable temperature and humidity conditions in the mushroom house, limited worker skills, and pest infestations. These conditions necessitate a structured and systematic risk management approach. This study aims to identify production risks, analyze their root causes, and formulate priority risk mitigation strategies to support business sustainability. This study employs a descriptive research design using qualitative and quantitative approaches. Primary data were collected through direct observation, in-depth interviews, and questionnaires administered to the owner and workers of UD. ARERA Oyster Mushroom. Risk identification was conducted using the Fishbone Diagram to classify root causes based on human, material, method, machine, and environmental factors. Risk prioritization was carried out using the House of Risk (HOR) method. HOR 1 was applied to determine priority risk agents based on Aggregate Risk Potential (ARP), while HOR 2 prioritized mitigation actions by evaluating effectiveness and implementation difficulty. The results indicate that the most critical production risks are inconsistent baglog quality, unstable environmental conditions, inadequate worker skills, and pest attacks. Priority mitigation strategies include establishing baglog quality standards, improving environmental control systems, providing technical training, and implementing regular pest management. The integration of Fishbone Diagram and House of Risk provides a comprehensive framework for proactive risk management in oyster mushroom cultivation.